(untitled) - Adler, Freda (New York, 2004)
This leading text for courses in Criminology is known for its lucid style, student-oriented approach, and its interdisciplinary global perspective. The Fourth Edition further underscores this unique student-centered approach by making a free student study CD ("Making the Grade") available with every copy of the text. A robust Online Learning Center featuring chapter quizzes with feedback, vocabulary flashcards, interactive exercises, and more is also available. The Adler text comes in two versions, one with, and the other without coverage of the criminal justice system. For schools that retain the traditional criminology course, which includes criminological coverage of criminal justice, Criminology and the Criminal Justice System, Fifth Edition, is the ideal text. For schools that offer a separate introductory course in criminal justice, Criminology, Fifth Edition is the appropriate text.
Keywords: Tội phạm học,Criminology